UNISON framework of system dynamics-based technology acquisition decision for semiconductor manufacturing and an empirical study. (March 2023) - Hong, Tzu-Yen; Chien, Chen-Fu; Chen, Hung-Pin
Highlights: A UNISON framework is proposed for technology acquisition decision. A system dynamic-based model is employed to evaluate the outcomes of the strategy. An empirical study is conducted in a case company with realistic data. Sensitivity analysis is conducted to investigate the impacts of key factors. Potential difficulties and benefits and the insight of management are discussed. Abstract: Semiconductor industry is technology-intensive and capital-intensive, in which semiconductor manufacturing companies strive to continuously migrate to advanced process technologies with productivity and quality to maintain competitive advantages effectively and efficiently. Since technology acquisition and capacity expansion take a long lead time, the present problem is a strategic decision under uncertainties that needs both human judgments and analytical approaches. Limitations of the existing studies can be traced in part to the lack of a framework within which different strategies can be evaluated while considering dynamic and uncertain market condition with systematic decision approaches. Focusing on realistic needs, this study aims to propose a framework for analyzing technology acquisition decisions with analytics based on historical data and conduct an empirical study for semiconductor manufacturing to reduce the risks and optimize the expected benefits. A system dynamic-based model was employed to clarify the dynamic interactions to evaluate the expected outcomes of the technology acquisition strategies. Moreover, sensitivity analysis is conducted to investigate the impacts of key factors to provide insights into different market scenarios for the decision-makers. The results of the empirical study have shown the practical viability of the proposed approach.